Examination of water for pollution control. a reference handbook - Suess, Michael J. (Pergamon Press, 1982)
Examination of Water for Pollution Control: A Reference Handbook, Volume 3: Biological, Bacteriological and Virological Examination is a part of a three-volume reference handbook that provides information and recommendations for setting up water pollution control programs and establishing a unified system for the analysis of fresh and waste water. This volume covers analytical procedures relevant to the examination of water organisms. A concise and systematic description of methods, such as sampling, storage, standardization, operation, and calculation relevant in quantifying variables concern.